Securing Development - Zoellick, Robert B. (World Bank, Washington, DC, 2018)
Robert B. Zoellick, President of the World Bank, remarked that the traumas of fragile states and the interconnections of globalization require our generation to recognize anew the nexus among economics, governance, and security. Most wars are now conflicts within states, and fragile states account for most of them. The "R" in IBRD has a new meaning: reconstructing Afghanistan, Cambodia, Côte d’Ivoire, Haiti, Iraq, Kosovo, Liberia, the Palestinian territories, the Solomon Islands, Southern Sudan, Timor-Leste, and other lands of conflict. One billion people live in fragile states. Zoellick provided ten priorities toward fragile states: 1) first, focus on building legitimacy of the state; 2) provide security; 3) building rule of law and legal order; 4) bolster local and national ownership; 5) ensure economic stability – as a foundation for growth and opportunity; 6) pay attention to the political economy; 7) crowd in the private sector; 8) coordinate across institutions and actors; 9) consider the regional context; 10) recognize the long-term commitment. He reviewed these principles in practice for Afghanistan, Haiti, and Liberia.